Can Salary Allocation Affect Winning Percentage In The National Hockey League? : - Holeksa, Zachary Thomas (2016)
The purpose of this paper is to provide insight into the most efficient allocation of salary in the National Hockey League, with respect to the positional groups of forwards, defensemen, and goaltenders. With the hypothesis that the most efficient method by which to allocate salary is disproportional between the three groups, three different regressions are run. The results of the regressions and subsequent tests confirm the hypothesis that teams should perform better if they do not allocate their available salary proportionally. It is found, holding spending on goaltenders constant, that teams should perform better if they invest more in either forwards or defensemen. The results are in support of previous papers, written by Marchand et al. (2007) and Simmons & Berri (2011), that an egalitarian pay system is not ideal.